A new species of Meteterakis Karve, 1930 (Nematoda: Heterakoidea) from Indotestudo elongata (Blyth) in China with a key to the species of Meteterakis - Zhang, Shuqian; Zhang, Luping (Zootaxa, 2011)
Meteterakis wangi sp. nov. was collected from the intestine of Indotestudo elongata (Blyth) from Shijiazhuang, Hebei Province, China by anthelminthic treatment. The new species differs from congeners by the shape and length of spicules, the number and arrangement of caudal papillae, and presence of gubernaculum. The name of M. bufonis Gambhir, Tarnita, Chinglenkhomba, Gyaneswori & Indranich, 2006 was preoccupied and is thus a junior secondary homonym of M. bufonis (Biswas & Charkavarty, 1963) Baker, 1984. We propose to rename the species as M. gambhiri nom. nov. A key to the species of the genus Meteterakis is also given.